Performance of Risk Assessment Indices for the Prediction of Postmenopausal Osteoporosis - Rezzan Günaydın,; Altınay Göksel Karatepe,; Taciser Kaya,; Uğur Karlıbaş, (Archives of Rheumatology, 2007)
Objective: To evaluate the performance of osteoporosis risk assessment indices in identifying women with osteoporosis. Patients and Methods: One-hundred eighty-six postmenopausal women aged 45 years and older were included in the study. The subjects were evaluated in terms of the risk for osteoporosis by using Osteoporosis Screening Tool (OST), Simple Calculated Osteoporosis Risk Estimation (SCORE), Osteoporosis Risk Assessment Instrument (ORAI), and Osteoporosis Index of Risk (OSIRIS). Bone mineral densities (BMD) at the lumbar spine and the proximal femur were measured by dual energy X-ray absorptiometry (DXA). The performance of indices in identifying subjects with osteoporosis (T-score ≥ -2.5) at the L2-4 spine or the femoral neck were evaluated using Receiver Operating Characteristic analysis and the areas under the curve (AUC) were calculated. Results: When the defined cut-off values (<2 for OST, >7 for SCORE, >8 for ORAI and <1 for OSIRIS) were used to send the patients for DXA testing, the sensitivity of the risk indices to identify osteoporosis at the femoral neck ranged from 72% to 86%, the specificity from 38% to 54%. At the lumbar spine, these values ranged from 58% to 73% for sensitivity and from 38% to 53% for specificity. The AUC values of indices ranged from 0,718 to 0,733 for osteoporosis at the femoral neck and from 0,541 to 0,579 for osteoporosis at the lumbar spine. Conclusion: It was observed that all four indices showed similar performance for identifying women with osteoporosis, and were more effective for identifying femoral neck osteoporosis. Utilization of these indices, because of their high negative predictive values, provide safe exclusion of healthy women who have a normal BMD and do not need a DXA testing, thus saving the DXA cost. It was concluded that the OST index could be preferred in clinical practice due to its ease of application. (Rheumatism 2007; 22: 48-54)